Integrating social-ecological systems and global production networks: local effects of trophy hunting in Namibian conservancies - Gargallo, E.; Kalvelage, L. (Development Southern Africa, 2021)
In addition to wildlife conservation, Community-Based Natural Resource Management (CBNRM) programmes aim to foster regional development. To achieve this, communal areas couple to tourism Global Production Networks (GPN). In this paper, we conceptualise Namibian communal Conservancies as Social-Ecological Systems (SES) and combine the SES and GPN approaches to benefit from the SESF's explanatory power for ecological and social relationships at a local level as well as from the GPN grasp of global linkages. We analyse the impact of trophy hunting on three communal conservancies in Namibia: King Nehale, Nyae Nyae, and Ehi-Rovipuka. Although wildlife numbers in these conservancies have increased, positive economic impacts are often insufficient, unevenly distributed across regions, and parts of the population are excluded. At the same time, findings indicate that in some areas, where revenues are larger and population is smaller, benefits from hunting can be significant and can contribute to SES sustainability.